Evaluation of the Bruker Biotyper Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry System for Identification of Clinical and Environmental Isolates of Burkholderia pseudomallei - Wang, He; Chen, Ya-Lei; Teng, Shih-Hua; Xu, Zhi-Peng; Xu, Ying-Chun; Hsueh, Po-Ren (Frontiers in Microbiology, 2016)
Burkholderia pseudomallei is not represented in the current version of Bruker Biotyper matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) system. A total of 66 isolates of B. pseudomallei, including 30 clinical isolates collected from National Taiwan University Hospital (NTUH, n=27) and Peking Union Medical College Hospital (PUMCH, n=3), and 36 isolates of genetically confirmed strains, including 13 from clinical samples and 23 from environmental samples, collected from southern Taiwan were included in this study. All these isolates were identified by partial 16S rDNA gene sequencing analysis and the Bruker Biotyper MALDI-TOF MS system. Among the 30 isolates initially identified as B. pseudomallei by conventional identification methods, one was identified as B. cepacia complex (NTUH) and three were identified as B. putida (PUMCH) by partial 16S rDNA gene sequencing analysis and Bruker Biotyper MALDI-TOF MS system. The Bruker Biotyper MALDI-TOF MS system misidentified 62 genetically confirmed B. pseudomallei isolates as B. thailandensis or Burkholderia species (score values, 1.803-2.063) when the currently available database (DB 5627) was used. However, using a newly created MALDI-TOF MS database (including B. pseudomallei NTUH-3 strain), all isolates were correctly identified as B. pseudomallei (score values >2.000, 100%). An additional 60 isolates of genetically confirmed B. cepacia complex and B. putida were also evaluated by the Bruker Biotyper MALDI-TOF MS system using the newly created database and none of these isolates were identified as B. pseudomallei. MALDI-TOF MS is a versatile and robust tool for the rapid identification of B. pseudomallei using the enhanced database.